Penggunaan teknologi digital ramah otak, ramah anak dan ramah lingkungan untuk pengajaran Pendidikan Agama Islam di SMA Negeri Kota Depok - Alwahid, Muhamad Azhar; Saepudin, Didin; Subagiya, Bahrum; Andriansyah, Andri; Andestend (Program Studi Magister Pendidikan Agama Islam, 2024)
This article aims to explain that brain-friendly, child-friendly and environment-friendly digital technology through interaction between teachers and students with comprehensive guidance can improve learning outcomes. With brain-friendly, child-friendly and environmentally-friendly technologies more channels of interaction between teachers and students are created so as to improve teaching and shape students' thinking patterns. In classroom learning teachers use WhatsApp, YouTube, Instagram, power points, google classroom, quizzes, Edmundo, google meet and zoom meeting. The learning approach used is the scientific approach (observing, questioning, gathering information, associating and communicating), so that learning becomes more interesting and students become more active. However, although digital technology can improve learning outcomes, it has not been able to achieve the main objectives of Islamic religious education, namely religiosity, faith, piety and noble character. In addition, brain-friendly, child-friendly and environmentally friendly technology has advantages but also has several weaknesses. The advantages of using brain-friendly, child-friendly and environmentally friendly technology are (1) making it easier for teachers and students to access knowledge; (2) there is no need to buy and stack books but teachers can access e-books (electronic books) from the internet which can be opened via a hand phone or laptop; (3) finding teaching materials and other needs becomes very easy; (4) communicating with others is so easy and fast; (5) making it easier for teachers to provide subject matter to students. Meanwhile, the disadvantages of using brain-friendly, child-friendly and environmentally friendly technology are as follows: (1) some students' thoughts have a tendency towards radical thinking; (2) the rise of plagiarism among students; (3) many students become lazy and tend to behave unruly and resist; (4) lazy to carry out worship, especially the five daily prayers; (5) making the main task as a side and spending time using the internet to find other information outside the tasks given by the teacher; (6) the emergence of arrogant behavior, namely the emergence of feelings from students feeling smarter than their teachers because students have more time to access various kinds of information that enter through the internet. Abstrak Artikel ini bertujuan menjelaskan bahwa teknologi digital ramah otak, ramah anak dan ramah lingkungan melalui interaksi antara guru dan siswa dengan bimbingan yang komprehensif dapat meningkatkan hasil pembelajaran. Dengan teknologi ramah otak, ramah anak dan ramah lingkungan semakin banyak saluran interaksi antara guru dan siswa diciptakan sehingga dapat meningkatkan pengajaran dan membentuk pola berpikir siswa. Dalam pembelajaran di kelas guru menggunakan WhatsApp, Youtube, Instagram, Power poin, Google Classroom, Quizzes, Edmundo, Google Meet dan Zoom Meeting. Pendekatan pembelajaran yang digunakan adalah pendekatan saintifik (mengamati, menanya, mengumpulkan informasi, mengasosiasi dan mengomunikasikan), sehingga pembelajaran menjadi lebih menarik dan siswa menjadi lebih aktif. Namun demikian walaupun teknologi digital dapat meningkatkan hasil pembelajaran akan tetapi belum bisa mencapai tujuan pendidikan agama Islam yang utama yaitu religiusitas, beriman, bertakwa dan berakhlak mulia. Selain itu teknologi ramah otak, ramah anak dan ramah lingkungan memiliki kelebihan tetapi juga memiliki beberapa kelemahan. Kelebihan penggunaan teknologi ramah otak, ramah anak dan ramah lingkungan adalah (1) memudahkan guru dan siswa dalam mengakses ilmu pengetahuan; (2) tidak perlu banyak membeli dan menumpuk buku tetapi guru dapat mengakses e-book (buku elektronik) dari internet yang dapat dibuka melalui handphone atau laptop; (3) mencari bahan ajar dan kebutuhan lain menjadi sangat mudah; (4) berkomunikasi dengan orang lain begitu mudah dan cepat; (5) memudahkan guru dalam memberikan materi pelajaran kepada siswa. Sedangkan kelemahan penggunaan teknologi ramah otak, ramah anak dan ramah lingkungan adalah sebagai berikut: (1) beberapa pemikiran siswa memiliki kecenderungan pada pemikiran radikal; (2) maraknya plagiarisme di kalangan para siswa; (3) banyak siswa menjadi malas dan cenderung berperilaku sulit diatur dan melawan; (4) malas melaksanakan ibadah terutama shalat lima waktu; (5) menjadikan tugas pokok sebagai sampingan dan menghabiskan waktu menggunakan internet untuk mencari informasi lain di luar tugas yang diberikan guru; (6) timbulnya tabiat sombong yaitu timbulnya perasaan dari siswa merasa lebih pintar dari gurunya karena siswa lebih banyak waktu untuk mengakses berbagai macam informasi yang masuk lewat internet.